Legal Protection for Consumers for Providing Digital Electronic Transaction Services - Ikbal Tawakal; Mohamad Tohari; Lamijan Lamijan (Return : Study of Management, Economic and Bussines, 2024)
In this increasingly advanced era of globalization, all human activities are aimed at being carried out efficiently and easily. With the growing use of the internet in the trade sector, there has been a shift in the relationship between sellers and buyers; they are becoming increasingly separated as they only interact through the internet without direct meetings. It also raises several legal issues related to the protection of transactions conducted on e-commerce platforms in Indonesia. However, the Consumer Protection Law (UUPK) and the Electronic Information and Transactions Law (UUITE) have provided a sufficient legal framework to protect consumers in e-commerce transactions, as outlined in various provisions in both laws.